Wear Performance of CBN Tool in Machining of ADI : Effect of Tool Life on Sintered Elements - FUJIMURA, Yoshio; SHINTANI, Kazuhiro; KATO, Hideharu (Transactions of the Japan Society of Mechanical Engineers Series C, 1991)
One of the difficult-to-machine materials, austempered bainitic spheroidal graphite cast iron (ADI), has been machined so far only by grinding. In this paper, the effect of tool life on sintered elements of CBN tools was investigated. Cutting of ADI was attempted with the different CBN tools of sintered, elements which consist of c-BN grain size, binding material and content rate in both the c-BN grain and binding phase. The CBN tools containing small-sized c-BN grains exhibited excellent wear resistance and surface roughness compared to that containing large-sized c-BN grains. The cutting performance of CBN tools is due to the influences on cracking in the c-BN grain by stress concentration and bonding strength in both the c-BN grain and binding phase. The content rate shows that the optimum combination of both the c-BN grain and binding phase is about 40c-BN grain/60 binding phase in which the thickness of the binding phase is 3μm. The optimum cutting condition is 1.67m/s from the standpoint of wear resistance and surface roughness.